Polishing composition, polishing method, and metho for manufacturing semiconductor substrate

By using a grinding composition containing grinding particles, inorganic salts and negatively charged organic compounds, the problem of maintaining the grinding speed ratio within a moderate range and reducing surface defects when grinding silicates and silicates efficiently in multilayer chip manufacturing is solved.

JP2025042789APending Publication Date: 2025-03-28FUJIMI INCORPORATED
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023149928
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-15
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

During the multilayer chip manufacturing process, it is difficult to maintain the silicate grinding speed within a moderate range while reducing defects on the silicate surface when grinding silicates and silicates efficiently.

Method used

A grinding composition comprising grinding particles, inorganic salts and negatively charged organic compounds is used, the composition has a pH value of less than 7.0, a conductivity of 10 mS/cm or higher, and the Zeta potential of the grinding particles is negative.

Benefits of technology

While efficiently grinding silicates, the grinding speed ratio of silicates and silicates is maintained within a moderate range and the defects on the silicate surface are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025042789000001
    Figure 2025042789000001
  • Figure 2025042789000002
    Figure 2025042789000002
Patent Text Reader

Abstract

To provide means by which the ratio of the polishing speed of silicon nitride to that of silicon oxide (selection ratio) can be kept within an appropriate range while polishing silicon nitride at a high polishing speed, and to reduce defects on the silicon oxide surface after polishing.SOLUTION: It is a polishing composition containing abrasive grains, inorganic salts, and an anionic organic compound, having a pH of less than 7.0, and the electrical conductivity of the polishing composition is greater than 10 mS / and the zeta potential of the abrasive grains in the polishing composition is negative.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polishing composition, a polishing method, and a method for producing a semiconductor substrate. [Background technology]

[0002] In recent years, new microfabrication technologies have been developed to accompany the high integration and high performance of LSI (Large Scale Integration). Chemical mechanical polishing (CMP) is one of these technologies, and is frequently used in the LSI manufacturing process, especially in the multi-layer wiring formation process, for planarizing interlayer insulating films, forming metal plugs, and forming buried wiring (damascene wiring).

[0003] The CMP has been applied to each process in semiconductor manufacturing, and one aspect of the invention is the application to a gate formation process in transistor manufacturing. When manufacturing a transistor, materials such as metal, silicon, silicon oxide, polycrystalline silicon, and silicon nitride may be polished, and there is a demand for polishing each material at high speed in order to improve productivity. In order to meet such a demand, for example, Patent Document 1 discloses a polishing composition that contains colloidal silica (sulfonic acid group (anion) modified colloidal silica) with an organic acid fixed thereto as an abrasive grain and has a pH of 6 or less, for the purpose of providing a polishing composition capable of polishing a polishing target having poor chemical reactivity such as silicon nitride at high speed. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2012-040671 A Summary of the Invention [Problem to be solved by the invention]

[0005] Recently, substrates containing both silicon oxide and silicon nitride have been used. For such substrates, there is an increasing demand to polish silicon nitride at a high polishing rate while polishing at an appropriate polishing rate ratio (selectivity ratio) (for example, polishing rate of silicon nitride / polishing rate of silicon oxide=1.0 or more and 4.0 or less), and to reduce defects on the silicon oxide surface after polishing.

[0006] The present invention has been made in view of the above circumstances, and has as its object to provide a means for polishing silicon nitride at a high polishing rate while keeping the ratio of the polishing rate of silicon nitride to the polishing rate of silicon oxide (selectivity) within an appropriate range and reducing defects on the silicon oxide surface after polishing. [Means for solving the problem]

[0007] The present inventors have conducted intensive research in view of the above problems, and have found that the above problems can be solved by a polishing composition that contains an abrasive grain, an inorganic salt, and an anionic organic compound, has a pH of less than 7.0, has an electrical conductivity of 10 mS / cm or more, and has a negative zeta potential of the abrasive grain in the polishing composition, and have completed the present invention. Effect of the Invention

[0008] According to the present invention, it is possible to provide a means for polishing silicon nitride at a high polishing rate while keeping the ratio of the polishing rate of silicon nitride to the polishing rate of silicon oxide (selectivity ratio) within an appropriate range and reducing defects on the surface of the object to be polished after polishing. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] According to one embodiment of the present invention, there is provided a polishing composition containing abrasive grains, an inorganic salt, and an anionic organic compound, and having a pH of less than 7.0, wherein the electrical conductivity of the polishing composition is 10 mS / cm or more, and the zeta potential of the abrasive grains in the polishing composition is negative. With such a polishing composition of the present invention, it is possible to polish silicon nitride at a high polishing rate while keeping the ratio of the polishing rate of silicon nitride to the polishing rate of silicon oxide (selectivity) within an appropriate range, and to reduce defects on the surface of the object to be polished (particularly silicon oxide) after polishing.

[0010] Although the details of why the polishing composition of the present invention provides the above-mentioned effects are unclear, it is believed that the mechanism is as follows. Note that the mechanism is based on speculation, and the technical scope of the present invention is not limited by the mechanism.

[0011] The polishing composition according to the present invention has a pH of less than 7.0, and under such conditions, the zeta potential of the silicon nitride surface is positive. Due to electrostatic attraction, the abrasive grains having a negative zeta potential contained in the polishing composition are easily attracted to the silicon nitride surface having a positive zeta potential, and the polishing rate of silicon nitride increases (for example, 600 Å / min or more). Furthermore, since the electrical conductivity of the polishing composition according to the present invention is 10 mS / cm or more, the ratio (selectivity) of the polishing rate of silicon nitride to the polishing rate of silicon oxide can be set within an appropriate range (for example, the polishing rate of silicon nitride / polishing rate of silicon oxide=1.0 or more and 4.0 or less).

[0012] Furthermore, according to the polishing composition of the present invention, defects (particularly scratches) on the surface of the object to be polished (particularly silicon oxide) after polishing can be reduced. One of the factors that increases scratches is thought to be that a complex is formed between the abrasive grains and organic residues (e.g. polishing pad debris), and the complex causes localized polishing. The anionic organic compound according to the present invention is easily adsorbed to organic residues (e.g. polishing pad debris). As a result, electrostatic repulsion occurs between the abrasive grains having a negative zeta potential and the organic residues, suppressing the formation of a complex between the abrasive grains and the organic residues, which is thought to suppress scratches.

[0013] The embodiments of the present invention will be described in detail below, but the present invention is not limited to the following embodiments and can be modified in various ways within the scope of the claims. The embodiments described in this specification can be combined in any way to form other embodiments. In this specification, unless otherwise specified, operations and measurements of physical properties are performed under conditions of room temperature (20°C to 25°C) and relative humidity of 40% RH to 50% RH.

[0014] [Abrasive grain] The polishing composition according to the present invention contains abrasive grains. The abrasive grains have the function of mechanically polishing an object to be polished, and increase the polishing rate of the object to be polished by the polishing composition.

[0015] In the polishing composition of the present invention, the abrasive grains have a negative zeta potential. Here, the "zeta (ζ) potential" refers to the potential difference that occurs at the interface between a solid and a liquid when they are in contact with each other and undergo relative motion. When the zeta potential of the abrasive grains is 0 mV or more (0 mV or positive), the polishing speed of silicon nitride decreases.

[0016] In the polishing composition of the present invention, the zeta potential of the abrasive grains is preferably -60 mV or more and -10 mV or less, more preferably -50 mV or more and -15 mV or less, and even more preferably -45 mV or more and -20 mV or less. When the abrasive grains have a zeta potential in such a range, the polishing speed of silicon nitride can be further improved.

[0017] Here, the zeta potential of the abrasive grains in the polishing composition is a value measured by the method described in the Examples. The zeta potential of the abrasive grains can be adjusted by the amount of anionic groups (particularly organic acid groups) contained in the abrasive grains described below, the pH of the polishing composition, etc.

[0018] The type of abrasive grain is not particularly limited, and examples thereof include metal oxides such as silica, alumina, zirconia, and titania. The abrasive grain may be used alone or in combination of two or more kinds. The abrasive grain may be a commercially available product or a synthetic product.

[0019] The type of abrasive grain is preferably silica, more preferably colloidal silica.The method for producing colloidal silica includes sodium silicate method and sol-gel method, and the colloidal silica produced by any method can be suitably used as the abrasive grain of the present invention.However, from the viewpoint of reducing metal impurities, the colloidal silica produced by the sol-gel method is preferred because it can be produced with high purity.

[0020] Colloidal silica can be produced by the sol-gel method using a conventionally known method. Specifically, colloidal silica can be obtained by using a hydrolyzable silicon compound (e.g., alkoxysilane or a derivative thereof) as a raw material and carrying out a hydrolysis-condensation reaction.

[0021] In some embodiments of the present invention, the colloidal silica contained in the polishing composition is preferably anion-modified colloidal silica (anion-modified colloidal silica), more preferably colloidal silica with organic acid fixed on the surface. Colloidal silica with organic acid fixed on the surface tends to have a larger absolute value of zeta potential in the polishing composition than normal colloidal silica with no organic acid fixed on the surface. Therefore, the zeta potential of colloidal silica in the polishing composition is easily adjusted to be negative.

[0022] Preferred examples of colloidal silica having an organic acid fixed to its surface include colloidal silica having an organic acid group, such as a carboxylic acid group, a sulfonic acid group, a phosphonic acid group, or an aluminic acid group, fixed to its surface. Among these, colloidal silica having a sulfonic acid or a carboxylic acid fixed to its surface is preferred from the viewpoint of ease of production, and colloidal silica having a sulfonic acid fixed to its surface (sulfonic acid fixed colloidal silica, sulfonic acid modified colloidal silica, sulfonic acid modified colloidal silica) is more preferred.

[0023] The immobilization of an organic acid on the surface of colloidal silica cannot be achieved by simply allowing colloidal silica and an organic acid to coexist. For example, if sulfonic acid, which is a type of organic acid, is to be immobilized on colloidal silica, it can be achieved by the method described in "Sulfonic acid-functionalized silica through quantitative oxidation of thiol groups", Chem. Commun. 246-247 (2003). Specifically, a silane coupling agent having a thiol group, such as 3-mercaptopropyltrimethoxysilane, is coupled to colloidal silica, and then the thiol group is oxidized with hydrogen peroxide to obtain colloidal silica with sulfonic acid immobilized on the surface (sulfonic acid immobilized colloidal silica, sulfonic acid modified colloidal silica).

[0024] Alternatively, when a carboxylic acid, which is a type of organic acid, is immobilized on colloidal silica, it can be carried out by, for example, the method described in "Novel Silane Coupling Agents Containing a Photolabile 2-Nitrobenzyl Ester for Introduction of a Carboxy Group on the Surface of Silica Gel", Chemistry Letters, 3, 228-229 (2000). Specifically, a silane coupling agent containing a photoreactive 2-nitrobenzyl ester is coupled to colloidal silica, followed by light irradiation, to obtain colloidal silica with a carboxylic acid immobilized on the surface (carboxylic acid-modified colloidal silica, carboxylic acid-modified colloidal silica).

[0025] The shape of the abrasive grains is not particularly limited, and may be spherical or non-spherical. Specific examples of non-spherical shapes include polygonal prisms such as triangular prisms and square prisms, cylinders, bales in which the center of a cylinder is bulged out more than the ends, donut shapes in which the center of a disk is penetrated, plates, so-called cocoon shapes with a constriction in the center, so-called association-type spheres in which multiple particles are integrated, so-called confetti shapes with multiple protrusions on the surface, and rugby ball shapes, and various other shapes are not particularly limited.

[0026] The size of the abrasive grains is not particularly limited. For example, the average primary particle diameter of the abrasive grains is preferably 5 nm or more, more preferably 8 nm or more, even more preferably 10 nm or more, and particularly preferably 12 nm or more. As the average primary particle diameter of the abrasive grains increases, the polishing speed of the object to be polished by the polishing composition increases. In addition, the average primary particle diameter of the abrasive grains is preferably 100 nm or less, more preferably 80 nm or less, and even more preferably 50 nm or less. As the average primary particle diameter of the abrasive grains decreases, it becomes easier to obtain a surface with fewer defects by polishing with the polishing composition. That is, the average primary particle diameter of the abrasive grains is preferably 5 nm or more and 100 nm or less, more preferably 8 nm or more and 80 nm or less, even more preferably 10 nm or more and 50 nm or less, and particularly preferably 12 nm or more and 50 nm or less. The average primary particle diameter of the abrasive grains can be calculated, for example, based on the specific surface area (SA) of the abrasive grains calculated by the BET method, assuming that the shape of the abrasive grains is a true sphere, and more specifically, the value measured by the method described in the Examples can be adopted.

[0027] In addition, the average secondary particle diameter of the abrasive grains is preferably 10 nm or more, more preferably 15 nm or more, even more preferably 20 nm or more, and particularly preferably 25 nm or more. As the average secondary particle diameter of the abrasive grains increases, the resistance during polishing decreases, and stable polishing becomes possible. In addition, the average secondary particle diameter of the abrasive grains is preferably 400 nm or less, more preferably 300 nm or less, even more preferably 200 nm or less, particularly preferably 100 nm or less, and most preferably 80 nm or less. As the average secondary particle diameter of the abrasive grains decreases, the surface area per unit mass of the abrasive grains increases, the contact frequency with the object to be polished increases, and the polishing speed increases. That is, the average secondary particle diameter of the abrasive grains is preferably 10 nm or more and 400 nm or less, more preferably 15 nm or more and 300 nm or less, even more preferably 20 nm or more and 200 nm or less, even more preferably 25 nm or more and 100 nm or less, and particularly preferably 25 nm or more and 80 nm or less. The average secondary particle size of the abrasive grains can be measured, for example, by a dynamic light scattering method such as a laser diffraction scattering method. Specifically, the value measured by the method described in the examples can be used.

[0028] The average degree of association of the abrasive grains is preferably 5.0 or less, more preferably 4.0 or less, even more preferably 3.0 or less, and particularly preferably 2.5 or less. As the average degree of association of the abrasive grains decreases, defects can be reduced more. The average degree of association of the abrasive grains is also preferably 1.0 or more, more preferably 1.5 or more, and even more preferably 2.0 or more. This average degree of association is obtained by dividing the value of the average secondary particle diameter of the abrasive grains by the value of the average primary particle diameter. As the average degree of association of the abrasive grains increases, there is an advantageous effect that the polishing speed of the object to be polished by the polishing composition improves.

[0029] The upper limit of the aspect ratio of the abrasive grains in the polishing composition is not particularly limited, but is preferably less than 2.0, more preferably 1.8 or less, and even more preferably 1.5 or less. In such a range, defects on the surface of the object to be polished can be further reduced. The aspect ratio is the average of the values ​​obtained by taking the smallest rectangle that circumscribes the image of the abrasive grains by a scanning electron microscope, and dividing the length of the long side of the rectangle by the length of the short side of the same rectangle, and can be determined using general image analysis software. The lower limit of the aspect ratio of the abrasive grains in the polishing composition is not particularly limited, but is preferably 1.0 or more, and more preferably 1.2 or more.

[0030] In the particle size distribution of abrasive grains obtained by laser diffraction scattering method, the lower limit of D90 / D10, which is the ratio of the particle diameter (D90) when the cumulative particle mass from the fine particle side reaches 90% of the total particle mass and the particle diameter (D10) when the cumulative particle mass from the fine particle side reaches 10% of the total particle mass of all particles, is not particularly limited, but is preferably 1.1 or more, more preferably 1.4 or more, even more preferably 1.7 or more, and most preferably 2.0 or more. In addition, in the particle size distribution of abrasive grains in a polishing composition obtained by laser diffraction scattering method, the upper limit of the ratio D90 / D10, which is the particle diameter (D90) when the cumulative particle mass from the fine particle side reaches 90% of the total particle mass and the particle diameter (D10) when the cumulative particle mass from the fine particle side reaches 10% of the total particle mass of all particles, is not particularly limited, but is preferably 3.0 or less, more preferably 2.5 or less. Within such a range, defects on the surface of the object to be polished can be further reduced.

[0031] The size of the abrasive grains (average primary particle size, average secondary particle size, aspect ratio, D90 / D10, etc.) can be appropriately controlled by selecting the manufacturing method of the abrasive grains, etc.

[0032] The concentration (content) of the abrasive grains is not particularly limited, but is preferably 0.5% by mass or more, more preferably 0.8% by mass or more, even more preferably 1% by mass or more, even more preferably more than 1% by mass, and particularly preferably 1.5% by mass or more, based on the total mass of the polishing composition. The concentration (content) of the abrasive grains is preferably 20% by mass or less, more preferably 15% by mass or less, even more preferably 10% by mass or less, and particularly preferably 5% by mass or less, based on the total mass of the polishing composition. That is, the concentration (content) of the abrasive grains is preferably 0.5% by mass or more and 20% by mass or less, more preferably 0.8% by mass or more and 20% by mass or less, even more preferably 1% by mass or more and 15% by mass or less, even more preferably more than 1% by mass and 10% by mass or less, and particularly preferably 1.5% by mass or more and 5% by mass or less, based on the total mass of the polishing composition. Within such a range, the polishing speed can be improved while suppressing costs. When the polishing composition contains two or more types of abrasive grains, the concentration (content) of the abrasive grains means the total amount of these.

[0033] [Inorganic salts] The polishing composition according to the present invention contains an inorganic salt. The inorganic salt mainly functions to adjust the electrical conductivity of the polishing composition to 10 mS / cm or more, which is believed to enable the ratio (selectivity) of the polishing rate of silicon nitride to the polishing rate of silicon oxide to be within an appropriate range (e.g., polishing rate of silicon nitride / polishing rate of silicon oxide=1.0 or more and 4.0 or less).

[0034] Examples of inorganic salts include inorganic salts composed of the following cations and anions. Examples of cations include alkali metal ions such as lithium ion, sodium ion, and potassium ion, alkaline earth metal ions such as magnesium ion, calcium ion, and strontium ion, polyatomic ions such as ammonium ion, and complex ions. Examples of anions include halide ions (fluoride ion, chloride ion, bromide ion, iodide ion, etc.), oxoacid ions (borate ion, carbonate ion, nitrate ion, nitrite ion, metasilicate ion, phosphate ion, monohydrogen phosphate ion, dihydrogen phosphate ion, phosphonate ion, monohydrogen phosphonate ion, phosphinate ion, sulfate ion, sulfonate ion, sulfite ion, thiosulfate ion, chromate ion, dichromate ion, permanganate ion, etc.), thiocyanate ion, cyanate ion, and sulfamate ion.

[0035] Specific examples of inorganic salts include lithium salts such as lithium chloride, lithium bromide, lithium carbonate, lithium nitrate, and lithium thiocyanate; calcium salts such as calcium chloride, calcium bromide, calcium carbonate, calcium nitrate, and calcium thiocyanate; iron salts such as iron nitrate and iron thiocyanate; potassium salts such as potassium chloride, potassium bromide, potassium nitrate, potassium sulfate, potassium thiocyanate, potassium sulfamate, potassium phosphate, potassium dihydrogen phosphate, potassium monohydrogen phosphate, and potassium monohydrogen phosphonate; sodium salts such as sodium chloride, sodium bromide, sodium nitrate, sodium sulfate, and sodium thiocyanate; zinc salts such as zinc chloride, zinc nitrate, and zinc thiocyanate; magnesium salts such as magnesium nitrate, magnesium sulfate, and magnesium thiocyanate; strontium salts such as strontium nitrate and strontium thiocyanate; ammonium chloride, ammonium bromide, ammonium iodide, ammonium nitrate, ammonium phosphate, ammonium dihydrogen phosphate, ammonium monohydrogen phosphate, ammonium phosphonate, ammonium monohydrogen phosphonate, ammonium sulfate, ammonium thiocyanate, and ammonium sulfamate. These inorganic salts may be used alone or in combination of two or more. In addition, the inorganic salts to be used may be commercially available products or synthetic products.

[0036] Among these, from the viewpoint of better exerting the effects of the present invention, an ammonium salt of an inorganic acid is preferable, and the inorganic acid is more preferably sulfuric acid or nitric acid, and therefore, the inorganic salt is more preferably ammonium sulfate or ammonium nitrate.

[0037] The concentration (content) of inorganic salt in the polishing composition is not particularly limited, but in the case of the polishing composition used as it is as a polishing liquid for polishing the object to be polished, the lower limit of the concentration (content) of inorganic salt in the polishing composition is preferably 0.05 mass% (500 mass ppm) or more, more preferably 0.1 mass% (1000 mass ppm) or more, and even more preferably 0.2 mass% (2000 mass ppm) or more, based on the total mass of the polishing composition.In addition, the upper limit of the concentration (content) of inorganic salt in the polishing composition is preferably 3.0 mass% (30000 mass ppm) or less, more preferably 2.5 mass% (25000 mass ppm) or less, and even more preferably 2.0 mass% (20000 mass ppm) or less, based on the total mass of the polishing composition.

[0038] That is, the concentration (content) of the inorganic salt is preferably 0.05 mass% or more and 3.0 mass% or less, more preferably 0.1 mass% or more and 2.5 mass% or less, and even more preferably 0.2 mass% or more and 2.0 mass% or less, relative to the total mass of the polishing composition.

[0039] When the polishing composition contains two or more kinds of inorganic salts, the concentration (content) of the inorganic salts means the total amount thereof.

[0040] [Anionic organic compounds] The polishing composition according to the present invention contains an anionic organic compound. The anionic organic compound is easily adsorbed to organic residues (e.g., polishing pad debris), and as a result, electrostatic repulsion can be generated between the abrasive grains having a negative zeta potential and the organic residues. This is believed to suppress the formation of a complex between the abrasive grains and the organic residues that may cause scratches, and reduce defects (especially scratches) on the silicon oxide surface.

[0041] In the present invention, the molecular weight of the anionic organic compound is preferably less than 1000, and more preferably not more than 800. The molecular weight means the sum of the atomic weights of the atoms constituting the anionic organic compound.

[0042] An anionic organic compound is an organic compound having an anionic group. An anionic group is a group that is negatively charged or forms an anion in water. Examples of the anionic group include an oxo acid group, an oxo acid base, and a hydroxyl group. Examples of the oxo acid group include a carboxylic acid group (carboxy group), a phosphonic acid group, a phosphoric acid group, a sulfonic acid group, and a sulfate group. Examples of the oxo acid base include salt groups of these oxo acid groups (alkali metal salts, alkaline earth metal salts, ammonium salts, etc.).

[0043] Further specific examples of the anionic organic compound include saturated or unsaturated aliphatic carboxylic acids such as formic acid, acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, caprylic acid, capric acid, undecanoic acid, tridecanoic acid, myristic acid, pentadecanoic acid, palmitic acid, heptadecanoic acid, isobutyric acid, isovaleric acid, isocaproic acid, ethylbutyric acid, methylvaleric acid, isocaprylic acid, propylvaleric acid, ethylcaproic acid, acrylic acid, crotonic acid, methacrylic acid, isocrotonic acid, 3-butenoic acid, pentenoic acid, hexenoic acid, heptenoic acid, octenoic acid, nonenoic acid, decenoic acid, undecenoic acid, dodecenoic acid, oleic acid, and 3-methylcrotonic acid; toluic acid, ethylbenzoic acid, propylbenzoic acid, isopropylbenzoic acid, butylbenzoic acid, isobutenoic acid, and the like. Examples of the anionic organic compound include aromatic carboxylic acids such as ethyl benzoic acid, sec-butyl benzoic acid, tert-butyl benzoic acid, resorcinol benzoic acid, hydroxybenzoic acid, and phenylacetic acid; methanesulfonic acid, ethanesulfonic acid, hexanesulfonic acid, octane sulfonic acid, 1,2-ethanedisulfonic acid, vinylsulfonic acid, (meth)allylsulfonic acid, p-toluenesulfonic acid, benzenesulfonic acid, xylenesulfonic acid, alkylbenzenesulfonic acids having an alkyl group of 8 to 24 carbon atoms such as n-dodecyl group, anthraquinonesulfonic acid, naphthalenesulfonic acid, naphtholsulfonic acid, and styrenesulfonic acid; and alkylsulfuric acids and hydroxyalkylsulfuric acids such as ethylsulfuric acid, laurylsulfuric acid, and hydroxyethylsulfuric acid. In addition, alkali metal salts, alkaline earth metal salts, and ammonium salts of these acid compounds can also be used as the anionic organic compound according to the present invention.

[0044] These anionic organic compounds may be used alone or in combination of two or more. In addition, the anionic organic compounds may be commercially available products or synthetic products.

[0045] Among the anionic organic compounds, from the viewpoint of further exerting the effects of the present invention, it is preferable to have at least one of a sulfonic acid group or a salt group thereof, and a sulfate group or a salt group thereof. More preferably, the anionic organic compound is at least one selected from the group consisting of sodium hexanesulfonate, sodium octanesulfonate, dodecylbenzenesulfonic acid, and sodium lauryl sulfate. In addition, it is preferable that the anionic organic compound has an alkyl group having 12 to 18 carbon atoms. By having such an alkyl group, defects (scratches) on the silicon oxide surface can be further reduced.

[0046] The concentration (content) of the anionic organic compound in the polishing composition is not particularly limited, but in the case of the polishing composition that is used as it is as a polishing liquid for polishing the object to be polished, the lower limit of the concentration (content) of the anionic organic compound in the polishing composition is preferably 0.0001 mass% (1 mass ppm) or more, more preferably 0.0005 mass% (5 mass ppm) or more, and even more preferably 0.0008 mass% (8 mass ppm) or more, based on the total mass of the polishing composition.In addition, the upper limit of the concentration (content) of the anionic organic compound in the polishing composition is preferably 0.1 mass% (1000 mass ppm) or less, more preferably 0.08 mass% (800 mass ppm) or less, and even more preferably 0.05 mass% (500 mass ppm) or less, based on the total mass of the polishing composition.

[0047] That is, the concentration (content) of the anionic organic compound is preferably 0.0001 mass% or more and 0.1 mass% or less, more preferably 0.0005 mass% or more and 0.08 mass% or less, and even more preferably 0.0008 mass% or more and 0.05 mass% or less, relative to the total mass of the polishing composition.

[0048] When the polishing composition contains two or more kinds of anionic organic compounds, the concentration (content) of the anionic organic compounds means the total amount thereof.

[0049] [Electrical Conductivity of Polishing Composition] The electrical conductivity (EC) of the polishing composition according to the present invention is 10 mS / cm or more. If the electrical conductivity is less than 10 mS / cm, the ratio (selectivity) of the polishing rate of silicon nitride to the polishing rate of silicon oxide is not within an appropriate range (i.e., the polishing rate of silicon nitride / polishing rate of silicon oxide is outside the range of 1.0 to 4.0). The electrical conductivity is preferably 11 mS / cm or more, more preferably 12 mS / cm or more. The upper limit of the electrical conductivity (EC) of the polishing composition according to the present invention is not particularly limited, but is preferably 40 mS / cm or less, more preferably 30 mS / cm or less, and even more preferably 15 mS / cm or less. That is, the electrical conductivity (EC) of the polishing composition according to the present invention is preferably 11 mS / cm or more and 40 mS / cm or less, more preferably 12 mS / cm or more and 30 mS / cm or less, and even more preferably 12 mS / cm or more and 15 mS / cm or less. The electrical conductivity of the polishing composition can be adjusted by the type and amount of inorganic salt, anionic organic compound, and pH adjuster described later, etc. The electrical conductivity (EC) of the polishing composition can be measured by the method described in the Examples.

[0050] [pH and pH adjusters] The pH of the polishing composition according to the present invention is less than 7.0. If the pH is 7.0 or more, the polishing rate of silicon nitride becomes insufficient. The pH is preferably 6.0 or less, more preferably 5.0 or less, and even more preferably less than 5.0. The pH is preferably 1.0 or more, more preferably 1.2 or more, and even more preferably 1.3 or more. That is, the pH of the polishing composition according to the present invention is preferably 1.0 or more and 6.0 or less, more preferably 1.0 or more and 5.0 or less, and even more preferably 1.0 or more and less than 5.0. The pH may be 1.2 or more and 6.0 or less, 1.2 or more and 5.0 or less, 1.2 or more and less than 5.0, 1.3 or more and 6.0 or less, 1.3 or more and 5.0 or less, or 1.3 or more and less than 5.0.

[0051] In the polishing composition of the present invention, the above-mentioned inorganic salt and anionic organic compound can also play the role of pH adjuster.However, when it is difficult to obtain desired pH by these compounds alone, it is preferable to add pH adjuster to adjust pH within the range that does not inhibit the effect of the present invention.

[0052] That is, the polishing composition according to some preferred embodiments of the present invention further contains a pH adjuster. The pH adjuster can contribute to adjusting the pH of the polishing composition by selecting the type and amount of the pH adjuster.

[0053] The pH adjuster is not particularly limited as long as it is a compound having a pH adjusting function, and known compounds can be used. Examples of such compounds include acids and alkalis.

[0054] Specific examples of acids that can be used as a pH adjuster include inorganic acids such as hydrochloric acid, sulfuric acid, nitric acid, hydrofluoric acid, boric acid, carbonic acid, hypophosphorous acid, phosphorous acid, and phosphoric acid.

[0055] Examples of bases that can be used as pH adjusters include amines such as aliphatic amines and aromatic amines, organic bases such as quaternary ammonium hydroxide, alkali metal hydroxides such as sodium hydroxide and potassium hydroxide, hydroxides of alkaline earth metals (group 2 elements), and ammonia.

[0056] The amount of pH adjuster to be added is not particularly limited, and can be appropriately adjusted so that the polishing composition has a desired pH. The pH of the polishing composition can be measured, for example, by a pH meter, and specifically, can be measured by the method described in Examples.

[0057] [Dispersion medium] The polishing composition according to the present invention preferably further contains a dispersion medium. Examples of the dispersion medium include water; alcohols such as methanol, ethanol, and ethylene glycol; ketones such as acetone, and mixtures thereof. Of these, water is preferred as the dispersion medium. That is, according to a more preferred embodiment of the present invention, the dispersion medium contains water. According to a more preferred embodiment of the present invention, the dispersion medium is substantially composed of water. Note that the above-mentioned "substantially" means that a dispersion medium other than water may be included as long as the object of the present invention can be achieved, and more specifically, the dispersion medium is preferably composed of 90% by mass or more and 100% by mass or less of water and 0% by mass or more and 10% by mass or less of a dispersion medium other than water, and more preferably composed of 99% by mass or more and 100% by mass or less of water and 0% by mass or more and 1% by mass or less of a dispersion medium other than water. Most preferably, the dispersion medium is water.

[0058] From the viewpoint of not inhibiting the action of the components contained in the polishing composition, it is preferable for the dispersion medium to be water that contains as few impurities as possible. Specifically, pure water or ultrapure water from which impurity ions have been removed with an ion exchange resin and then foreign matter has been removed through a filter, or distilled water is more preferable.

[0059] [Other ingredients] The polishing composition of the present invention may further contain other components such as water-soluble polymer, complexing agent, metal corrosion inhibitor, preservative, antifungal agent, reducing agent, surfactant, etc. Hereinafter, the preservative and antifungal agent, which are preferred components, will be described. Also, the oxidizing agent will be described.

[0060] (Preservatives and fungicides) Examples of preservatives and antifungal agents that can be added to the polishing composition of the present invention include isothiazoline preservatives such as 2-methyl-4-isothiazolin-3-one and 5-chloro-2-methyl-4-isothiazolin-3-one, paraoxybenzoic acid esters, and phenoxyethanol, etc. These preservatives and antifungal agents may be used alone or in combination of two or more.

[0061] (Oxidizing agent) The polishing composition according to the present invention is preferably substantially free of an oxidizing agent. If an oxidizing agent is contained in the polishing composition, the surface of the object to be polished may be oxidized to generate an oxide film, which may result in a longer polishing time. Specific examples of the oxidizing agent include hydrogen peroxide (H2O2), sodium persulfate, ammonium persulfate, and sodium dichloroisocyanurate. The term "substantially free of an oxidizing agent" means that the polishing composition does not contain an oxidizing agent at least intentionally. Therefore, a polishing composition that inevitably contains a small amount of an oxidizing agent due to raw materials, manufacturing method, etc. is included in the concept of a polishing composition that does not substantially contain an oxidizing agent. For example, the concentration (content) of the oxidizing agent relative to the total mass of the polishing composition is preferably less than 0.01% by mass (100 ppm by mass), more preferably 0.005% by mass (50 ppm by mass) or less. The lower limit of the concentration (content) of the oxidizing agent is preferably 0% by mass or more, more preferably 0.0005% by mass (5 ppm by mass) or more.

[0062] [Form of polishing composition] The polishing composition according to the present invention is typically supplied to an object to be polished in the form of a polishing liquid containing the polishing composition, and is used to polish the object to be polished. The polishing composition according to the present invention may be used as a polishing liquid after dilution (typically diluted with water), or may be used as a polishing liquid as it is. That is, the concept of the polishing composition according to the present invention includes both a polishing composition (working slurry) that is supplied to an object to be polished and used to polish the object to be polished, and a concentrated liquid (original working slurry liquid) that is diluted and used for polishing. The concentration ratio of the concentrated liquid can be, for example, about 2 to 100 times on a volume basis, and is usually about 3 to 50 times.

[0063] [Polished object] The object to be polished according to the present invention is not particularly limited, and examples thereof include single crystal silicon, polycrystalline silicon (polysilicon), polycrystalline silicon doped with n-type or p-type impurities, amorphous silicon, amorphous silicon doped with n-type or p-type impurities, silicon oxide, silicon nitride, silicon carbonitride (SiCN), metals, SiGe, carbon-containing materials, and the like.

[0064] Examples of objects to be polished that contain silicon oxide include a TEOS-type silicon oxide film (hereinafter simply referred to as "TEOS" or "TEOS film") produced using tetraethyl orthosilicate as a precursor, a high density plasma (HDP) film, an undoped silicate glass (USG) film, a phosphorus silicate glass (PSG) film, a boron-phosphorus silicate glass (BPSG) film, and a rapid thermal oxidation (RTO) film.

[0065] Examples of metals include tungsten, copper, aluminum, cobalt, hafnium, nickel, gold, silver, platinum, palladium, rhodium, ruthenium, iridium, and osmium.

[0066] Examples of carbon-containing materials include amorphous carbon, spin-on carbon (SOC), diamond-like carbon (DLC), nanocrystalline diamond, graphene, low-k materials such as SiOC (carbon-containing silicon oxide in which SiO2 is doped with C), silicon carbide, etc. Films containing carbon-containing materials can be formed by CVD, PVD, spin coating, etc.

[0067] The object to be polished may be a commercially available product or may be produced by a known method.

[0068] Among these, objects to be polished containing silicon oxide and silicon nitride are preferred. Therefore, according to a preferred embodiment of the present invention, the polishing composition is used for polishing objects to be polished containing silicon oxide and silicon nitride.

[0069] [Method of manufacturing the polishing composition] The method for producing the polishing composition according to the present embodiment is not particularly limited, and can be obtained by, for example, stirring and mixing abrasive grains, inorganic salt, anionic organic compound, and other additives added as necessary. The details of each component are as described above.

[0070] The temperature at which the components are mixed is not particularly limited, but is preferably 10° C. to 40° C. Heating may be performed to increase the dissolution rate. The mixing time is also not particularly limited as long as the components can be mixed uniformly.

[0071] [Polishing method and semiconductor substrate manufacturing method] As described above, the polishing composition according to this embodiment is particularly suitable for use in polishing an object having silicon nitride. Thus, the present invention provides a polishing method for polishing an object containing silicon oxide and silicon nitride with the polishing composition according to this embodiment. The present invention also provides a method for producing a semiconductor substrate, comprising polishing a semiconductor substrate containing silicon oxide and silicon nitride by the above-mentioned polishing method.

[0072] As a polishing device, a general polishing device can be used that is equipped with a holder for holding a substrate or the like having an object to be polished, a motor whose rotation speed can be changed, and a polishing platen onto which a polishing pad (polishing cloth) can be attached.

[0073] The polishing pad may be made of any material, including general nonwoven fabric, polyurethane, porous fluororesin, etc. It is preferable that the polishing pad has grooves formed thereon to allow the polishing liquid to accumulate.

[0074] Regarding the polishing conditions, for example, the rotation speed of the polishing table (platen) and carrier (head) was 10 rpm (0.17 s -1 ) or more 500rpm (8.33s -1 The pressure applied to the substrate having the object to be polished (polishing pressure) is preferably 0.5 psi (3.45 kPa) or more and 10 psi (68.9 kPa) or less.

[0075] The method of supplying the polishing composition to the polishing pad is not particularly limited, and for example, a method of continuously supplying the composition using a pump, etc. is adopted. There is no limit to the amount of the composition supplied, but it is preferable that the surface of the polishing pad is always covered with the polishing composition according to the present invention.

[0076] The polishing composition according to the present embodiment may be a one-liquid type or a multi-liquid type such as a two-liquid type. The polishing composition according to the present invention may be prepared by diluting the stock solution of the polishing composition with a diluting solution such as water, for example, 2 to 100 times, usually 3 to 50 times, on a volume basis.

[0077] [Polishing speed] As described above, the polishing composition of the present invention is capable of polishing silicon nitride at a high polishing rate.

[0078] In the present invention, the polishing speed for silicon nitride is preferably 600 Å / min or more, and may be 605 Å / min or more, 610 Å / min or more, 615 Å / min or more, 620 Å / min or more, 625 Å / min or more, 630 Å / min or more, 635 Å / min or more, 640 Å / min or more, 650 Å / min or more, or 660 Å / min or more.

[0079] [Selection ratio] As described above, the polishing composition of the present invention can control the ratio (selectivity) of the polishing rate of silicon nitride to the polishing rate of silicon oxide within an appropriate range.

[0080] In the present invention, the ratio of the polishing rate of silicon nitride to the polishing rate of silicon oxide (selectivity ratio, polishing rate of silicon nitride / polishing rate of silicon oxide) is preferably 1.0 or more, more preferably 1.2 or more, even more preferably 1.4 or more, even more preferably 1.5 or more, and particularly preferably 2.0 or more. The ratio of the polishing rate of silicon nitride to the polishing rate of silicon oxide is preferably 4.0 or less, more preferably 3.7 or less, even more preferably 3.5 or less, and particularly preferably 3.0 or less. That is, the selectivity may be 1.0 or more and 4.0 or less, 1.0 or more and 3.7 or less, 1.0 or more and 3.5 or less, or 1.0 or more and 3.0 or less. The selectivity may be 1.2 or more and 4.0 or less, 1.2 or more and 3.7 or less, 1.2 or more and 3.5 or less, or 1.2 or more and 3.0 or less. The selectivity may be 1.4 or more and 4.0 or less, 1.4 or more and 3.7 or less, 1.4 or more and 3.5 or less, or 1.4 or more and 3.0 or less. The selectivity may be 1.5 or more and 4.0 or less, 1.5 or more and 3.7 or less, 1.5 or more and 3.5 or less, or 1.5 or more and 3.0 or less. The selectivity may be 2.0 or more and 4.0 or less, 2.0 or more and 3.7 or less, 2.0 or more and 3.5 or less, or 2.0 or more and 3.0 or less. If the selectivity is out of the above range, the surface condition of the polished object (especially silicon oxide) finally obtained after polishing may be poor.

[0081] [scratch] As described above, the polishing composition of the present invention can reduce defects (eg, scratches) on the surface of an object to be polished (particularly silicon oxide) after polishing.

[0082] In some embodiments of the present invention, the number of scratches on the surface of the object to be polished (particularly silicon oxide) after polishing is usually less than 50, preferably less than 40, more preferably less than 30, and even more preferably less than 20. The lower limit of the number of scratches is 0. In this specification, a scratch refers to a flaw on the surface of the object to be polished that has a depth of 10 nm or more and less than 100 nm, a width of 100 nm or more and less than 500 nm, and a length of 80 nm or more. The number of scratches can be measured by the method described in the Examples.

[0083] Although the embodiments of the present invention have been described in detail, it is apparent that the same are illustrative and exemplary, not restrictive, and the scope of the present invention should be interpreted by the appended claims.

[0084] The present invention encompasses the following aspects and configurations. 1. A polishing composition comprising an abrasive grain, an inorganic salt, and an anionic organic compound and having a pH of less than 7.0, wherein the electrical conductivity of the polishing composition is 10 mS / cm or more, and the zeta potential of the abrasive grain in the polishing composition is negative. 2. The polishing composition according to 1 above, wherein the anionic organic compound has a molecular weight of less than 1,000. 3. The polishing composition according to 1 or 2 above, wherein the anionic organic compound has at least one of a sulfonic acid group or a salt group thereof, and a sulfate group or a salt group thereof. 4. The polishing composition according to any one of 1. to 3. above, wherein the anionic organic compound is at least one selected from the group consisting of sodium hexanesulfonate, sodium octanesulfonate, dodecylbenzenesulfonic acid, and sodium lauryl sulfate. 5. The polishing composition according to any one of 1. to 4. above, wherein the inorganic salt is an ammonium salt of an inorganic acid. 6. The polishing composition according to claim 5, wherein the inorganic acid is sulfuric acid or nitric acid. 7. The polishing composition according to any one of 1. to 6. above, wherein the abrasive grains are anion-modified colloidal silica. 8. The polishing composition according to any one of 1. to 7. above, wherein the pH is 1.0 or more and less than 5.0. 9. The polishing composition according to any one of 1. to 8. above, wherein the abrasive grains in the polishing composition have a zeta potential of more than -45 mV and -20 mV or less. 10. The polishing composition according to any one of 1. to 9. above, further comprising a dispersion medium. 11. The polishing composition according to any one of 1. to 10. above, which is substantially free of an oxidizing agent. 12. The polishing composition according to any one of 1. to 11. above, which is used for polishing an object containing silicon oxide and silicon nitride. 13. The polishing composition according to 12 above, wherein the ratio of the polishing rate of the silicon nitride to the polishing rate of the silicon oxide (polishing rate of silicon nitride / polishing rate of silicon oxide) is 1.0 or more and 4.0 or less. 14. A polishing method comprising the step of polishing an object containing silicon oxide and silicon nitride with the polishing composition according to any one of 1. to 13. 15. A method for producing a semiconductor substrate, comprising the step of polishing a semiconductor substrate containing silicon oxide and silicon nitride by the polishing method described in 14 above. EXAMPLES

[0085] The present invention will be described in more detail using the following examples and comparative examples. However, the technical scope of the present invention is not limited to the following examples. Unless otherwise specified, "%" and "parts" mean "% by mass" and "parts by mass", respectively. In the following examples, unless otherwise specified, the operations were performed under the conditions of room temperature (20°C to 25°C) / relative humidity 40% RH to 50% RH. Each physical property was measured as follows.

[0086] <Average primary particle size of abrasive grains> The average primary particle size of the abrasive grains was calculated from the specific surface area of ​​the silica particles measured by the BET method using "Flow Sorb II 2300" manufactured by Micromeritics, and the density of the abrasive grains.

[0087] <Average secondary particle size of abrasive grains> The average secondary particle diameter of the abrasive grains was measured as the volume average particle diameter (arithmetic mean diameter based on volume; Mv) using a dynamic light scattering particle size / particle size distribution analyzer UPA-UT151 (manufactured by Nikkiso Co., Ltd.).

[0088] <Zeta potential of abrasive grains> The zeta potential of the abrasive grains in the polishing composition was measured by subjecting the polishing composition to a Zetasizer Nano manufactured by Malvern Panalytical and measuring it using the laser Doppler method (electrophoretic light scattering measurement method) at a measurement temperature of 25°C, and calculating the zeta potential by analyzing the obtained data using the Smoluchowski formula.

[0089] <pH of polishing composition> The pH of the polishing composition was measured using a glass electrode type hydrogen ion concentration indicator (Model number: F-23, manufactured by Horiba, Ltd.) and three-point calibration was performed using standard buffer solutions (phthalate pH buffer solution, pH: 4.01 (25°C), neutral phosphate pH buffer solution, pH: 6.86 (25°C), carbonate pH buffer solution, pH: 10.01 (25°C)).The glass electrode was then placed in the polishing composition and the pH value was recorded after stabilization for at least 2 minutes.

[0090] <Electrical Conductivity of Polishing Composition> The electrical conductivity (EC) of the polishing composition was measured with a tabletop electrical conductivity meter (manufactured by Horiba, Ltd., model number: DS-71 LAQUA (registered trademark)).

[0091] <Sulfonic acid immobilized colloidal silica> The sulfonic acid-fixed colloidal silica (anion-modified colloidal silica) contained in the polishing composition was prepared by using colloidal silica having an average primary particle size of 34 nm, an average secondary particle size of 70 nm, and an average degree of association of 2.1, according to the method described in "Sulfonic acid-functionalized silica through quantitative oxidation of thiol groups", Chem. Commun. 246-247 (2003).

[0092] Example 1 <Preparation of Polishing Composition> To the water as a dispersion medium, sulfonic acid-fixed colloidal silica (average primary particle size: 34 nm, average secondary particle size: 70 nm, cocoon-shaped) as an abrasive grain was added so that the final concentration was 2.0 mass%. Furthermore, ammonium sulfate (manufactured by Kanto Chemical Co., Ltd.) as an inorganic salt was added so that the final concentration was 0.6 mass% (6000 mass ppm), and n-dodecylbenzenesulfonic acid (manufactured by Kanto Chemical Co., Ltd.) as an anionic organic compound was added so that the final concentration was 10 mass ppm, and stirring and mixing were performed (stirring temperature: 25°C, stirring time: 20 minutes). Furthermore, the pH was adjusted to 2.0 using nitric acid, and polishing composition 1 was completed. The electrical conductivity of the obtained polishing composition 1 was 14 mS / cm, and the zeta potential of the abrasive grains in the polishing composition 1 was -40 mV.

[0093] Example 2 Polishing composition 2 was prepared in the same manner as in Example 1, except that ammonium lauryl sulfate (Sigma-Aldrich) was used instead of n-dodecylbenzenesulfonic acid. The electrical conductivity of the obtained polishing composition 2 was 14 mS / cm, and the zeta potential of the abrasive grains in the polishing composition 2 was -40 mV.

[0094] Example 3 Polishing composition 3 was prepared in the same manner as in Example 1, except that sodium octanesulfonate (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) was used instead of n-dodecylbenzenesulfonic acid. The electrical conductivity of the obtained polishing composition 3 was 14 mS / cm, and the zeta potential of the abrasive grains in polishing composition 3 was -40 mV.

[0095] Example 4 Polishing composition 4 was prepared in the same manner as in Example 1, except that sodium hexanesulfonate (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) was used instead of n-dodecylbenzenesulfonic acid. The electrical conductivity of the obtained polishing composition 4 was 14 mS / cm, and the zeta potential of the abrasive grains in polishing composition 4 was -40 mV.

[0096] Example 5 Polishing composition 5 was prepared in the same manner as in Example 1, except that the amount of ammonium sulfate added was changed to an amount that gave a final concentration of 0.15 mass% (1500 mass ppm). The electrical conductivity of the obtained polishing composition 5 was 10 mS / cm, and the zeta potential of the abrasive grains in the polishing composition 5 was -40 mV.

[0097] Example 6 Except for using ammonium nitrate instead of ammonium sulfate, polishing composition 6 was prepared in the same manner as in Example 1. The electrical conductivity of the obtained polishing composition 6 was 14 mS / cm, and the zeta potential of the abrasive grains in the polishing composition 6 was -40 mV.

[0098] Comparative Example 1 Except for not using ammonium sulfate and n-dodecylbenzenesulfonic acid, Comparative Polishing Composition 1 was prepared in the same manner as in Example 1. The electrical conductivity of the obtained Comparative Polishing Composition 1 was 7 mS / cm, and the zeta potential of the abrasive grains in Comparative Polishing Composition 1 was -40 mV.

[0099] Comparative Example 2 Except for not using n-dodecylbenzenesulfonic acid, Comparative Polishing Composition 2 was prepared in the same manner as in Example 1. The electrical conductivity of the obtained Comparative Polishing Composition 2 was 14 mS / cm, and the zeta potential of the abrasive grains in Comparative Polishing Composition 2 was -40 mV.

[0100] Comparative Example 3 Except for not using ammonium sulfate, Comparative Polishing Composition 3 was prepared in the same manner as in Example 1. The electrical conductivity of the obtained Comparative Polishing Composition 3 was 7 mS / cm, and the zeta potential of the abrasive grains in Comparative Polishing Composition 3 was -40 mV.

[0101] Comparative Example 4 Except for changing the amount of ammonium sulfate added to an amount such that the final concentration was 0.001 mass% (10 mass ppm), Comparative Polishing Composition 4 was prepared in the same manner as in Example 1. The electrical conductivity of the obtained Comparative Polishing Composition 4 was 8 mS / cm, and the zeta potential of the abrasive grains in Comparative Polishing Composition 4 was -40 mV.

[0102] The compositions of the polishing compositions of Examples and Comparative Examples are shown in the following Table 1. In addition, "-" in the following Table 1 means that the component is not contained.

[0103] [Table 1] [evaluation] The following (1) and (2) were prepared as objects to be polished, and polishing was performed under the following conditions: (1) Silicon nitride film (Si3N4 film): A silicon wafer (200 mm, blanket wafer) with a 2000 Å thick silicon nitride film (Si3N4 film) formed on the surface. (2) Silicon oxide film (TEOS film): A silicon wafer (200 mm, blanket wafer) with a 10,000 Å-thick TEOS-type silicon oxide (SiO2) film formed on its surface.

[0104] (Polishing equipment and polishing conditions) Polishing equipment: Applied Materials 200mm CMP single-sided polishing equipment Mirra Polishing pad: Nitta Haas IC1010 hard polyurethane pad Grinding pressure: 2.5psi (1psi=6894.76Pa) Polishing platen rotation speed: 47 rpm Head (carrier) rotation speed: 43 rpm Supply of polishing composition: free-flowing Polishing composition supply amount: 200mL / min Polishing time: 60 seconds.

[0105] <Polishing speed> The thickness of each polished object before and after polishing was measured using an optical film thickness measuring device (ASET-f5x: manufactured by KLA-Tencor Corporation). The film thickness was measured using an optical film thickness measuring device (ASET-f5x: manufactured by KLA-Tencor Corporation).

[0106] The polishing rate for each object was calculated by dividing the difference in film thickness before and after polishing [(thickness before polishing) - (thickness after polishing)] by the polishing time. Regarding the polishing rate ratio between silicon nitride film and silicon oxide film, if the polishing rate of silicon nitride film / polishing rate of silicon oxide film (Si3N4 / SiO2 in Table 1) is 1.0 or more and 4.0 or less, it is practical.

[0107] <Number of scratches> The number of scratches on the silicon oxide surface after polishing was measured by measuring the coordinates of the entire surface of both sides of the polishing object (excluding the outer periphery of 2 mm) using a wafer inspection device "Surfscan (registered trademark) SP2" manufactured by KLA-Tencor Co., Ltd., and observing all the measured coordinates with a Review-SEM (RS-6000, manufactured by Hitachi High-Technologies Corporation). Scratches were counted as scratches on the substrate surface with a depth of 10 nm or more but less than 100 nm, a width of 100 nm or more but less than 500 nm, and a length of 80 nm or more. The fewer the number of scratches, the better. A scratch number of less than 50 is practical, preferably less than 40, more preferably less than 30, and even more preferably less than 20.

[0108] The evaluation results of the polishing rate and the number of scratches are shown in the following Table 2. In the following Table 2, the silicon nitride film is represented as "Si3N4" and the silicon oxide film is represented as "SiO2".

[0109] [Table 2] As is clear from Table 2 above, when the polishing composition of the Example was used, the polishing rate of silicon nitride was high, the ratio of the polishing rate of silicon oxide to the polishing rate of silicon oxide (selectivity ratio) was in an appropriate range, and the number of scratches on the silicon oxide surface was small. On the other hand, when the polishing composition of the Comparative Example was used, at least one of the polishing rate ratio and the number of scratches was deteriorated.

Claims

1. Abrasive grains and Inorganic salts, an anionic organic compound; and having a pH of less than 7.0, The polishing composition has an electrical conductivity of 10 mS / or more, A polishing composition, wherein the abrasive grains in the polishing composition have a negative zeta potential.

2. The polishing composition according to claim 1 , wherein the anionic organic compound has a molecular weight of less than 1,000.

3. The polishing composition according to claim 1 , wherein the anionic organic compound has at least one of a sulfonic acid group or a salt thereof, and a sulfate group or a salt thereof.

4. 2. The polishing composition according to claim 1, wherein the anionic organic compound is at least one selected from the group consisting of sodium hexanesulfonate, sodium octanesulfonate, dodecylbenzenesulfonic acid, and sodium lauryl sulfate.

5. The polishing composition according to claim 1 , wherein the inorganic salt is an ammonium salt of an inorganic acid.

6. The polishing composition according to claim 5 , wherein the inorganic acid is sulfuric acid or nitric acid.

7. The polishing composition according to claim 1 , wherein the abrasive grains are anion-modified colloidal silica.

8. The polishing composition according to claim 1 , wherein the pH is 1.0 or more and less than 5.

0.

9. 2. The polishing composition according to claim 1, wherein the abrasive grains in the polishing composition have a zeta potential of more than -45 mV and not more than -20 mV.

10. The polishing composition according to claim 1 , further comprising a dispersion medium.

11. The polishing composition of claim 1 , which is substantially free of an oxidizing agent.

12. 2. The polishing composition according to claim 1, which is used for polishing an object containing silicon oxide and silicon nitride.

13. 13. The polishing composition according to claim 12, wherein the ratio of the polishing rate of said silicon nitride to the polishing rate of said silicon oxide (polishing rate of silicon nitride / polishing rate of silicon oxide) is 1.0 or more and 4.0 or less.

14. 14. A polishing method comprising the step of polishing an object containing silicon oxide and silicon nitride with the polishing composition according to claim 1.

15. A method for producing a semiconductor substrate, comprising a step of polishing a semiconductor substrate containing silicon oxide and silicon nitride by the polishing method according to claim 14.

Citation Information

Patent Citations

  • Polishing composition and polishing method using the same

    JP2012040671A